PERANCANGAN APLIKASI E-COMMERCE DAN PENGELOLAAN DATA INVENTORI BERBASIS WEB PADA DAYA RAGA TEKNINDO - Albertus Ferdinand Pratono; Tony (Fakultas Teknologi Informasi Universitas Tarumanagara, 2025)
Daya Raga Teknindo is a company engaged in the production of stainless steel wire clothes hangers, seeking to increase sales and maintain consistent production data. Currently, recording of production activities is still done manually using paper and Microsoft Excel, which risks resulting in inconsistencies and loss of data. To overcome these challenges, the company plans to develop a web-based application that includes several key features. The company profile feature is designed as a marketing tool so that people can get to know the company better, while the e-commerce feature aims to make it easier for customers to buy products online. Apart from that, this application will provide an admin dashboard as a means of consistently managing inventory data and production activities. With this application, it is hoped that Daya Raga Teknindo can increase sales, manage data better and make more effective business decisions.